Development of peltier cooling system for automotive - Mohamed, Amir Izzani; Oumer, Ahmed Nurye; Jadin, Mohd Shawal (2017)
Nowadays, air-conditioning system of automobile arises to such many problems such as CFC emission that cause air pollution, the usage of fuel is increased and engine performance is decreased. Moreover, the current air-conditioning system is not capable to be used when the engine is not moving. Even when the vehicle is moving the use of air-conditioning system may increase fuel consumption This scenario could be subdued by the introduction of thermoelectric device as an alternating cooling option for car interior. Fuel usage decrease by using this pollution option and reduce engine performance can be prevented since the letter option was in the bracket of ‘Go Green’ region. The project is to make the automotive cabin being cooled by using thermoelectric cooler that can be applied on the car even when the engine is not moving. The system should be automatically turned on when the engine of the car is stop depending on the temperature inside and outside of the car. This temperature can be controlled by temperature sensor. The project is using the source of the automobile battery.